SURVEY ON POWER QUALITY ASSESSMENT OF WIND ENERGY AND SOLAR ENERGY WITH INNOVATIVE DEVICES (International Journal of Food and Nutritional Sciences, 2022)
This paper investigates power quality challenges in wind and solar energy systems and assesses the impact of innovative devices on improving system performance. With the increasing penetration of renewables, addressing issues like voltage fluctuations, harmonics, and reactive power imbalances is crucial for grid stability. This study reviews advanced technologies such as Dynamic Voltage Restorers (DVR), Static Synchronous Compensators (STATCOM), and Unified Power Quality Conditioners (UPQC) to evaluate their effectiveness in mitigating these challenges.